2011
DOI: 10.1089/ten.tea.2010.0461
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Bone Marrow Stromal Cells in a Syngenic Model of Bone Formation

Abstract: Bone marrow stromal cells (BMSCs) have been demonstrated to induce bone formation when associated to osteoconductive biomaterials and implanted in vivo. Nevertheless, their role in bone reconstruction is not fully understood and rare studies have been conducted to follow their destiny after implantation in syngenic models. The aim of the present work was to use sensitive and quantitative methods to track donor and recipient cells after implantation of BMSCs in a syngenic model of ectopic bone formation. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 48 publications
(73 reference statements)
5
17
0
Order By: Relevance
“…Cells were shown to survive at least two weeks in vivo , but with a decreasing bioluminescent signal after one week. This has been supported in a similar subcutaneous model, as applied in the present work, where implanted MSCs did not survive more than three weeks after implantation [30]. Without perivascular cells, vascular maturation is impaired leading to an endothelium prone to regression [10,11].…”
Section: Discussionsupporting
confidence: 71%
“…Cells were shown to survive at least two weeks in vivo , but with a decreasing bioluminescent signal after one week. This has been supported in a similar subcutaneous model, as applied in the present work, where implanted MSCs did not survive more than three weeks after implantation [30]. Without perivascular cells, vascular maturation is impaired leading to an endothelium prone to regression [10,11].…”
Section: Discussionsupporting
confidence: 71%
“…The lack of bone formation could also be related to the death of implanted cells. Indeed, converging data have recently reported that grafted MSC do not survive more than 3 weeks, notably after subcutaneous implantation into nude mice [11].…”
Section: Discussionmentioning
confidence: 98%
“…Also, a major concern related to procedures involving MSC is the fate of cells after they enter the host via massive implantation. It remains unknown whether these MSC remain at the grafted site and are specifically responsible for new bone formation, as suggested by some authors [23], [24], or if they die early after implantation and release mediators for cell recruitment from the local environment, as suggested in more recent studies [25][27].…”
Section: Introductionmentioning
confidence: 98%